Danggui-Shaoyao-San Attenuates Cognitive Impairment via the Microbiota–Gut–Brain Axis With Regulation of Lipid Metabolism in Scopolamine-Induced Amnesia - Liu, Piaoxue; Zhou, Xun; Zhang, Haoran; Wang, Rui; Wu, Xiaolang; Jian, Wenxuan; Li, Weirong; Yuan, Dongsheng; Wang, Qi; Zhao, Wei (Frontiers in Immunology, 2022)
Danggui-Shaoyao-San has a long history of being used as a traditional medicine (TCM) and has been reported to show therapeutic effect on alleviating the symptoms of Alzheimer’s disease (AD). The purpose of this study was to investigate whether DSS treatment attenuates cognitive impairment via the microbiota-gut-brain axis in scopolamine-induced amnesia. In this work, we first performed Morris water maze (MWM) test and novel object recognition (NOR) test to evaluate the memory function of C57BL/6N mice treated. Then we evaluated 16S rRNA for gut microbiota analysis, as well as assessment of blood-brain barrier function and intestinal barrier function and lipid metabolism analysis on tissues from scopolamine-fed mice. We hypothesized that DSS may affect brain function and behaviour through the gut-brain axis in a bidirectional interplay with both top-down and bottom-up regulation. Furthermore, in order to confirm whether intestinal flora plays the crucial role in scopolamine-induced amnesia, C57BL/6N mice were treated with fecal microbial transplantation (FMT) and then were performed behavioral tests. The mice’s feces were simultaneously evaluated by 16S rRNA analysis. The result supported the FMT-induced improvement in cognitive function highlights the role of the gut microbiota-brain axis to mediate cognitive function and behaviour. Collectively, these findings indicated that DSS altered lipid metabolism by activating LXR- PPAR-γ and repaired mucosal barrier dysfunction assessed with a broad range of techniques, which attenuated cognitive impairment via microbiota-gut-brain axis.